Contribution to FE modeling for intraoperative pedicle screw strength prediction. Issue 1 (2nd January 2018) - Van den Abbeele, Maxim; Valiadis, Jean-Marc; Lima, Lucas V. P. C.; Khalifé, Pascal; Rouch, Philippe; Skalli, Wafa
Abstract: Although the use of pedicle screws is considered safe, mechanical issues still often occur. Commonly reported issues are screw loosening, screw bending and screw fracture. The aim of this study was to develop a Finite Element (FE) model for the study of pedicle screw biomechanics and for the prediction of the intraoperative pullout strength. The model includes both a parameterized screw model and a patient-specific vertebra model. Pullout experiments were performed on 30 human cadaveric vertebrae from ten donors. The experimental force-displacement data served to evaluate the FE model performance. μCT images were taken before and after screw insertion, allowing the creation of an accurate 3D-model and a precise representation of the mechanical properties of the bone. The experimental results revealed a significant positive correlation between bone mineral density (BMD) and pullout strength (Spearman ρ  = 0.59, p  < 0.001) as well as between BMD and pullout stiffness (Spearman ρ  = 0.59, p  < 0.001). A high positive correlation was also found between the pullout strength and stiffness (Spearman ρ  = 0.84, p  < 0.0001). The FE model was able to reproduce the linear part of the experimental force-displacement curve. Moreover, a high positive correlation was found between numerical and experimental pullout stiffness (Pearson ρ  = 0.96, p  < 0.005) and strength (Pearson ρ  = 0.90, p  < 0.05). Once fully validated, this model opens the way for a detailed study of pedicle screw biomechanics and for future adjustments of the screw design.